2009
DOI: 10.1002/j.2050-0416.2009.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Coloured Wine Produced from Roselle (Hibiscus sabdariffa) Calyx Extract

Abstract: J. Inst. Brew. 115(2), 91-94, 2009Wine was produced from roselle (Hibiscus sabdariffa) calyx extract using strains of Saccharomyces cerevisiae and subjected to physico-chemical analyses using standard analytical methods. Imported commercial red wine was used as the reference for sensory evaluation. The results showed that ameliorated roselle calyx extract (must) had 4.21% protein, 0.69% titratable acidity, and 21°Brix total soluble solids. The roselle calyx wine had a pH value of 3.43, a titratable acidity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 9 publications
3
29
0
5
Order By: Relevance
“…Previous studies have reported the influence of incorporating roselle extracts on the biochemical and organoleptic properties of wine and yogurt (Alobo & Offonry, 2009;Iwalokun & Shittu, 2007). As a strong competing candidate in the field of functional foods, the impact of probiotic bacteria, Lactobacillus plantarum inoculation on the volatile profile of roselle infusion was also evaluated in this study.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported the influence of incorporating roselle extracts on the biochemical and organoleptic properties of wine and yogurt (Alobo & Offonry, 2009;Iwalokun & Shittu, 2007). As a strong competing candidate in the field of functional foods, the impact of probiotic bacteria, Lactobacillus plantarum inoculation on the volatile profile of roselle infusion was also evaluated in this study.…”
Section: Introductionmentioning
confidence: 98%
“…This may be due to the higher concentration of substrate available for the activity of yeast during the initial period of fermentation during which maximum amount of sugars was reduced to alcohol and CO 2 90:10 (grape:mahua) sample was found to have least TSS (3.5) indicating that it was best fermented. Alobo and Offonry [14] reported a gradual decrease in TSS with a corresponding increase in alcohol content. The significance of difference between sample 100:0, 95:5 and 90:10 (grape:mahua) was assessed using Tukey's test.…”
Section: Composition Of Wine After Fermentationmentioning
confidence: 95%
“…However, any fruit with a good proportion of sugar may be used for wine production (Alobo & Offonry, 2009). In Nigeria, there is abundance of tropical fruit including sweet oranges, which are highly perishable, and susceptible to bacterial and fungal contamination; as a result, they fail to reach the market due to spoilage, mechanical damage and over ripeness (Ihekoroye and Ngoddy, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The production of wines from common fruits could help reduce the level of post-harvest losses and increase variety of wines (Okoro, 2007;Alobo and Offonry, 2009). …”
Section: Introductionmentioning
confidence: 99%